2021
DOI: 10.21203/rs.3.rs-919325/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence of overweight and its associated risk factors among adolescents: A cross-sectional study in peri-urban area of Nepal

Abstract: Background Adolescence, being a crucial stage for experimentation and acceptance of new behavioral and lifestyle choices, is detrimental to their nutritional status. The nutritional status of adolescents being shaped by socio-cultural, environmental, and economic factors has also been impacted by their food habits and level of physical activity. The current nutritional shift and rapid urbanization had emerged overweight as an additional burden for consistently prevalent undernutrition issues. So, the study ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Twenty‐one studies explored differences between rural and urban areas and the majority of them (16 studies) (Bellundagi et al, 2022; Bhargava et al, 2016; Biswas et al, 2017; Chakraborty et al, 2018; Ganie et al, 2017; Goonapienuwala et al, 2022; Harding et al, 2019; Hombaiah et al, 2021; Islam et al, 2020; Khan et al, 2022; Khatri et al, 2021; Mohan et al, 2019; Pandurangi et al, 2022; Prasad et al, 2016; Yadav et al, 2018; Young et al, 2020) found a higher prevalence of overweight and/or obesity in urban areas. Differences in overweight/obesity prevalence for males and females were inconsistent across studies; however, a pooled analysis combining 2416 population‐based measurements found that BMI was higher among girls compared to boys in South Asia (NCD Risk Factor Collaboration (NCD‐RisC), 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐one studies explored differences between rural and urban areas and the majority of them (16 studies) (Bellundagi et al, 2022; Bhargava et al, 2016; Biswas et al, 2017; Chakraborty et al, 2018; Ganie et al, 2017; Goonapienuwala et al, 2022; Harding et al, 2019; Hombaiah et al, 2021; Islam et al, 2020; Khan et al, 2022; Khatri et al, 2021; Mohan et al, 2019; Pandurangi et al, 2022; Prasad et al, 2016; Yadav et al, 2018; Young et al, 2020) found a higher prevalence of overweight and/or obesity in urban areas. Differences in overweight/obesity prevalence for males and females were inconsistent across studies; however, a pooled analysis combining 2416 population‐based measurements found that BMI was higher among girls compared to boys in South Asia (NCD Risk Factor Collaboration (NCD‐RisC), 2017).…”
Section: Resultsmentioning
confidence: 99%